ROLE OF WAGES, INDUSTRIAL SECTOR AND THE GDP AGAINST JOB OPPORTUNITIES IN NGAWI REGENCY PERIOD 1987 - 2015 - Diyan Roffiani Puspitasari; Akhmad Daerobi; Siti Aisyah (Universitas Ahmad Dahlan, 2017)
This study aimed to analyze the influence of the regional minimum wage, the number of industrial and Gross Domestic Product (GDP) on employment in Ngawi year period 1987-2015. This research is explanatory because it is used in testing hypotheses.The unit of analysis in this study is data on the regional minimum wage, the number of industrial and Gross Domestic Product (GDP) and employment opportunities in Ngawi-year period from 1987 to 2015 were obtained from the Central Statistics Agency of East Java Province. Data were analyzed using Error Correction Model (ECM). The study found that: regional minimum wage, the number of industrial and Gross Regional Domestic Product (GRDP) a positive role in promoting employment in Ngawi-year period 1987-2015